Third generation continuous flow left ventricular assist devices; a comparative outcome analysis by device type. (14th October 2021) - Mihalj, M; Heinisch, P.P; Schober, P; Dobner, S; Fuerholz, M; Martinelli, M; Hugi-Mayr, B; De By, T.M.M.H; Mohacsi, P; Schefold, J.C; Luedi, M.M; Kadner, A; et al.
Abstract: Background: Continuous-flow left ventricular assist devices (CF-LVADs) have become a standard of care in end-stage heart failure (HF). Device-related complications remain high. Limited data exists comparing outcomes of the HeartMate 3 (HM3) and the HeartWare HVAD (HW). We aimed to analyze HM3 and HW devices implanted over the past 10 years with a focus on long-term clinical outcomes of respective patients. Methods: Investigator-initiated comparative, retrospective observational analysis of all patients who underwent primary implantation of a centrifugal CF-LVAD at our tertiary care academic center between January 2010 and December 2020. Data derived from a prospective registry, and included all patients receiving a HM3 or HW device. Primary endpoint was overall (all-cause) mortality and heart transplantation. Secondary endpoints included device-related major adverse cardiac and cerebrovascular events (MACCE), as well right heart failure (RHF), gastrointestinal (GI) bleeding, driveline infections, and surgical re-interventions. Results: Out of 106 primary CF-LVAD implantations, 36 (34%) received HM3 and 70 (66%) received HW. Median follow-up time was 1.48 years [interquartile range 0.67, 2.41] and did not differ between devices (p=0.739). HM3 was more often implanted in men (91.7% vs. 72.9%, p=0.024), patients were older (median 61 years [54, 66.5] vs. 52.5 years [43, 60], p<0.001), had a higher body mass index (BMI) (median 26.7 kg/m 2 [23.4, 29.0] vs. 24.3 kg/m 2 [20.7, 27.4], p=0.013), had more comorbidities and were more likely targeted for destination therapy (DT) (36.1% vs. 14.3%, p=0.010). Death occurred in 33.3% of HM3 patients, compared to 22.9% of HW patients, p=0.247 (probability of survival at 2 years 54.7% vs. 74.1%, p=0.296). After adjustment for confounders, we observed a significant 6-fold risk increase in device malfunctions for HW (hazard ratio (HR) 6.49, 95% CI [1.89, 22.32], p=0.003), but no significant differences between devices in pump thrombosis (p=0.173) or overall survival (p=0.801). Conclusions: Comparing long-term outcomes between HeartMate 3 and HeartWare HVAD for LVAD support from a prospective registry, HeartWare HVAD patients had a significantly higher risk of device malfunctions. No significant differences were evident between devices in overall survival, and in respect to most clinical outcomes. Funding Acknowledgement: Type of funding sources: None.